Supporting history of art with colorimetry: the paintings of Amadeo de Souza-Cardoso - Montagner, Cristina (2018)
Colour is a key element in paintings but its quantitative analysis is seldom used as an interpretative element in the context of the history of art. Here, we show how this can be accomplished by measuring and analyzing the colours of the paintings of the influential Portuguese painter Amadeo de Souza-Cardoso (1887-1918). His last paintings have been classified by arthistoriansasthe mostsuccessful andareconsidered a chromatically homogeneous nucleus in his career. However, there are no quantitative data supporting these considerations. To access this we compared 24 of his paintings (1911-17) using hyperspectral imaging data. From estimates of the number of colours that can be perceived in each painting we show that in the later works Amadeo has expanded the range of colours by including more hues and more levels of lightness. Moreover,thepaintingsdatedfrom1917havesimilarchromaticdistributionsincolour space. This colorimetric analysis revealed to be an important tool that provides quantitative support to the hypothesis formulated by art historians.